Biodegradable β‐Cyclodextrin Conjugated Gelatin Methacryloyl Microneedle for Delivery of Water‐Insoluble Drug. Issue 11 (4th May 2020) - Zhou, Xingwu; Luo, Zhimin; Baidya, Avijit; Kim, Han‐jun; Wang, Canran; Jiang, Xing; Qu, Moyuan; Zhu, Jixiang; Ren, Li; Vajhadin, Fereshteh; Tebon, Peyton; Zhang, Niyuan; et al.
Abstract: Transdermal delivery of water‐insoluble drugs via hydrogel‐based microneedle (MN) arrays is crucial for improving their therapeutic efficacies. However, direct loading of water‐insoluble drug into hydrophilic matrices remains challenging. Here, a biodegradable MN array patch that is fabricated from naturally derived polymer conjugates of gelatin methacryloyl and β ‐cyclodextrin (GelMA‐ β ‐CD) is reported. When curcumin, an unstable and water‐insoluble anticancer drug, is loaded as a model drug, its stability and solubility are improved due to the formation of an inclusion complex. The polymer‐drug complex GelMA‐ β ‐CD/CUR can be formulated into MN arrays with sufficient mechanical strength for skin penetration and tunable drug release profile. Anticancer efficacy of released curcumin is observed in three‐dimensional B16F10 melanoma models. The GelMA‐ β ‐CD/CUR MN exhibits relatively higher therapeutic efficacy through more localized and deeper penetrated manner compared with a control nontransdermal patch. In vivo studies also verify biocompatibility and degradability of the GelMA‐ β ‐CD MN arrays patch. Abstract : A hydrogel microneedle (MN) patch based on naturally derived gelatin methacryloyl and β ‐cyclodextrin conjugates is developed for transdermal delivery of water‐insoluble drugs. Tunable drug release profiles and enhanced drug stability are demonstrated via curcumin as a model drug. The newly developed MN patch possesses good biocompatibility that can potentially be used for various pharmaceutical applications.